Adapting total quality management for general practice: evaluation of a programme. Issue 3 (September 1996) - Lawrence, M; Packwood, T
Abstract : OBJECTIVE: Assessment of the benefits and limitations of a quality improvement programme based on total quality management principles in general practice over a period of one year (October 1993-4). DESIGN: Questionnaires to practice team members before any intervention and after one year. Three progress reports completed by facilitators at four month intervals. Semistructured interviews with a sample of staff from each practice towards the end of the year. SETTING: 18 self selected practices from across the former Oxford Region. Three members of each practice received an initial residential course and three one day seminars during the year. Each practice was supported by a facilitator from their Medical Audit Advisory Group. MEASURES: Extent of understanding and implementation of quality improvement methodology. Number, completeness, and evaluation of quality improvement projects. Practice team members' attitudes to and involvement in team working and quality improvement. RESULTS: 16 of the 18 practices succeeded in implementing the quality improvement methods. 48 initiatives were considered and staff involvement was broad. Practice members showed increased involvement in, and appreciation of, strategic planning and team working, and satisfaction from improved patients services. 11 of the practices intend to continue with the methodology. The commonest barrier expressed was time. CONCLUSION: Quality improvement programmes based on total quality management principles produce beneficial changes in service delivery and team working in most general practices. It is incompatible with traditional doctor centred practice. The methodology needs to be adapted for primary care to avoid quality improvement being seen as separate from routine activity, and to save time.